Care network for women in situation of violence: the challenges of care transversality - Angelina Lettiere; Ana Márcia Spanó Nakano (Universidade Federal de Goias, 2015)
A qualitative study aimed to understand how is configured the care for women in situation of violence, under the sight of professionals. Data was collected by interviews with seven key-informants, and it was analyzed by the method of interpretation of meanings. In the central theme category: auto eco-organizer system of institutions, two meaning nucleus were identified: Care axis and Institution Functionality. In the first, the care axis was classified as psychosocial care, health care and police care. At the institution functionality, attention to women was found while obtaining demands and referrals through triage. From the professional's perspective, although advances were obtained on the past years, the "mismatch" still persists in the care network for women in situation of violence, which does not contemplates what is conceived by attention transversality. The study pointed aids to strengthen the network, aiming to guarantee women's rights.